Development Of The Interactive Method "Micro-Macro Interpretation Cycle" (MMIC) - Sanabarkhon Siddikova Mahammadaliyevna (Next Scientists International Journal EIJP, 2026)
This article presents the development and theoretical justification of an interactive physics teaching method—the "Micro-Macro Interpretive Cycle" (MMIC)—aimed at developing students' conscious understanding of molecular-kinetic and thermodynamic concepts. The relevance of this study stems from persistent difficulties in mastering the fields of molecular physics and thermodynamics, due to their highly abstract nature and the probabilistic nature of the processes being studied. The proposed method is based on a step-by-step organization of learning activities, ensuring a cyclical transition from macroscopic observation of physics phenomena to their microscopic explanation and subsequent statistical generalization, leading to the application of the acquired knowledge in new situations. The article describes the structure of the method, defines its didactic functions, and demonstrates the potential for integrating phenomenological and statistical approaches in physics teaching. The results of theoretical analysis and pedagogical modeling indicate that the use of the MMIC method reduces the need for formal memorization of educational material, develops students' analytical and statistical thinking, and fosters a holistic scientific worldview. The method can be recommended for use in teaching molecular physics and thermodynamics in academic lyceums and technical educational institutions.